Rancang Bangun Aplikasi E-Tiket Pada PT Mitra Bahana Engineering Berbasis Web - Rafli; M. Irham (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The use of information technology can increase the efficiency and effectiveness of business processes in an organization. The E-Ticket application is one solution to minimize the level of errors and can help in managing the distribution of information and data. PT. Mitra Bahana Engineering, a company that operates in the field of mechanical and electrical planning for multi-storey buildings, still uses conventional methods in the supervision and management of projects that are less efficient and effective. Therefore, a system is needed that can manage projects more effectively and efficiently. The research method used is the Waterfall method and system modeling using UML (unified modeling language) developed using the Laravel. The testing phase in the design of this application uses blackbox testing. The result of this research is an E-Ticket application that can facilitate project management and progress reports and improve the efficiency and effectiveness of business processes at PT. Mitra Bahana Engineering. Thus, this study aims to design and build an E-Ticket application at PT. Mitra Bahana Engineering to facilitate project management and progress reports and improve the efficiency and effectiveness of business processes.